Silicon incorporated morpholine antifungals: design, synthesis, and biological evaluation - Jachak, Gorakhnath R.; Ramesh, Remya; Sant, Duhita G.; Jorwekar, Shweta U.; Jadhav, Manjusha R.; Tupe, Santosh G.; Deshpande, Mukund V.; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
Known morpholine class antifungals (fenpropimorph, fenpropidin, and amorolfine) were synthetically modified through silicon incorporation to have 15 sila-analogues. Twelve sila-analogues exhibited potent antifungal activity against different human fungal pathogens such as Candida albicans, Candida glabrata, Candida tropicalis, Cryptococcus neoformans, and Aspergillus niger. Si la-analogue 24 (fenpropimorph analogue) was the best in our hands, which showed superior fungicidal potential than fenpropidin, fenpropimorph, and amorolfine. The mode of action of sila-analogues was similar to morpholines, i.e., inhibition of sterol reductase and sterol isomerase enzymes of ergosterol synthesis pathway.
Keywords: Antifungal drugs; Candida albicans; ergosterol biosynthesis; morpholines; sila-analogues

Synthesis and antifungal potential of 1,2,3-triazole and 1,2,4-triazole thiol substituted strobilurin derivatives - Chaudhary, Preeti M.; Tupe, Santosh G.; Jorwekar, Shweta U.; Sant, Duhita G.; Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Deshpande, Mukund V. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2015)
beta-Methoxyacrylate group is an important pharmacophore of commercially used strobilurin fungicides. In the present study, a total of seventeen 1,2,4-triazole thiols 8a-h and 1,2,3-triazole substituted 10a-i strobilurin derivatives have been synthesized. 1,2,4-Triazole thiol substituted strobilurin derivatives 8a-h have been found to inhibit the growth of plant pathogens such as Fusarium oxysporum, Magnaporthe grisea, Drechslera oryzae and human pathogens Aspergillus fumigatus and different strains of Cryptococcus neoformans, with MIC in the range of 16-256 mu g/mL. In case of Candida albicans tested strain, the MIC is > 256 mu g/mL. p-Chlorophenyl substituted 1,2,4-triazole thiol strobiulrin derivative 8e is the most potent inhibitor with MIC of 16-64 mu g/mL against most of the tested pathogens. Antifungal action of the compounds is due to inhibition of mitochondrial respiration. In the resazurin reduction assay, EC50 for inhibition of RZ reduction in D. oryzae by azoxystrobin and 8e are 3.42 +/- 0.03 mu g/mL and 3.63 +/- 0.21 mu g/mL, respectively; while in case of C. neoformans, EC50,, of azoxystrobin and 8e are between 0.65-0.85 mu g/mL. In a non-pathogenic model Benjaminiella poitrasii, though the MIC for all the synthesized compounds 8a-h and 10a-i are > 256 mu g/ml, yeast to hypha transition is inhibited in the range of 21-75% at 4 mu g/mL concentration while EC50 for inhibition of RZ reduction by azoxystrobin and 8e are 31.5 +/- 0.4 mu g/mL and 17.95 +/- 0.7 mu g/mL, respectively. The 50% germ tube formation inhibition in case of C. albicans is observed at 108.49 mu g/mL. 1,2,4-Triazole thiol substituted strobilurin derivatives hold promise for the control of pathogenic fungi in agriculture and health care.
Keywords: 1; 2; 3-triazole strobilurin; 4-triazole thiol strobilurin; antifungal; Strobilurin; Y-H transition inhibition

Synthesis and biological evaluation of new fluconazole β-lactam conjugates linked via 1,2,3-triazole - Divse, Jaisingh M.; Mhaske, Santosh B.; Charolkar, Chaitanya R.; Sant, Duhita G.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Pore, Vandana S. (New Journal of Chemistry, 2017)
Novel 1,2,3-triazole-linked β-lactam–fluconazole conjugates 12(a–l) were designed and synthesized. The compounds showed potent antifungal activity against two pathogenic Candida strains; Candida albicans ATCC 24433 and Candida albicans ATCC 10231 with MIC values in the range of 0.0625–2 μg mL−1. Compounds 12h, 12j and 12k showed promising antifungal activity against all the tested fungal pathogens except C. neoformans ATCC 34554 compared to fluconazole. Compound 12j in which the β-lactam ring was formed using para-anisidine and benzaldehyde was found to be more potent than fluconazole against all the fungal strains with an IC50 value of <0.015 μg mL−1 for Candida albicans (ATCC 24433). Mechanistic studies for active compounds revealed that the antifungal action was due to ergosterol inhibition. Compounds 12h and 12j at a concentration of 0.125 μg mL−1 caused 91.5 and 96.8% ergosterol depletion, respectively, compared to fluconazole which at the same concentration caused 49% ergosterol depletion. The molecular docking study revealed that all the fluconazole β-lactam conjugates 12(a–l) could snugly fit into the active site of lanosterol 14α-demethylase (CYP51) with varying degrees of affinities. As anticipated, the binding energy for compound 12j (−58.961 kcal mol−1) was much smaller than that for fluconazole (−52.92 kcal mol−1). The synthesized compounds have therapeutic potential for the control of candidemia.